Ni-Catalyzed Asymmetric Allylation of Secondary Phosphine Oxides - Liu, Xu-Teng; Zhang, Ya-Qian; Han, Xue-Yu; Sun, Shi-Ping; Zhang, Qing-Wei (Journal of the American Chemical Society, 2019)
A nickel-catalyzed asymmetric allylation of secondary phosphine oxides (SPO) for the synthesis of tertiary phosphine oxides (TPO) was realized with high enantioselectivity. The dynamic kinetic asymmetric transformation of SPO was accomplished in the presence of nickel complex. By elucidating the absolute configurations of the reacted SPO starting material and the TPO product, we confirmed that the allylation reaction proceeded through a P-stereo retention process. The protocol represents the first example of synthesizing P-stereogenic phosphine oxides by allylation reaction.